2000
DOI: 10.1103/physrevlett.85.880
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Probe-Based Frequency-Dependent Microrheology of Polymer Gels and Biological Cells

Abstract: A new scanning probe-based microrheology approach is used to quantify the frequency-dependent viscoelastic behavior of both fibroblast cells and polymer gels. The scanning probe shape was modified using polystyrene beads for a defined surface area nondestructively deforming the sample. An extended Hertz model is introduced to measure the frequency-dependent storage and loss moduli even for thin cell samples. Control measurements of the polyacrylamide gels compare well with conventional rheological data. The ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
359
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(391 citation statements)
references
References 17 publications
27
359
2
3
Order By: Relevance
“…Such a sharp tip induces high local strains that can exceed the linear regime, thus introducing artifacts in the determination of the cell's mechanical properties (14,15). To avoid such artifacts, an alternative technique is often used where a micrometric bead is attached to the tip of the AFM cantilever (16)(17)(18). In AFM, the applied force is deduced from the deformation of the cantilever, whose measurement requires the use of an optical sensor, most commonly a system of photodiodes collecting a laser beam reflected by the cantilever.…”
Section: Introductionmentioning
confidence: 99%
“…Such a sharp tip induces high local strains that can exceed the linear regime, thus introducing artifacts in the determination of the cell's mechanical properties (14,15). To avoid such artifacts, an alternative technique is often used where a micrometric bead is attached to the tip of the AFM cantilever (16)(17)(18). In AFM, the applied force is deduced from the deformation of the cantilever, whose measurement requires the use of an optical sensor, most commonly a system of photodiodes collecting a laser beam reflected by the cantilever.…”
Section: Introductionmentioning
confidence: 99%
“…This research confirmed that the hydrodynamic drag force exhibits a locally pure viscous behavior and that the drag factor is dependent upon distance between the tip and the substrate. The authors pointed out that previous attempts to correct AFM measurements for hydrodynamic drag effects consisted of estimating the drag force at some distance above the specimen and then using this value to correct the measurements taken on contact [21][22][23]. However, it is expected that this approach will lead to an underestimation of the actual hydrodynamic drag at contact and the authors noted that applying corrective drag force measurements taken at even a few microns above the sample can lead to significant errors in the measured forces.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rheological properties of in vitro F-actin networks are quite different from those of cells: the magnitude of the elastic modulus typically underestimates that measured in cells, often by several orders of magnitude. In addition, unlike the linear behavior assumed for cells [1][2][3]10], the viscoelasticity of F-actin networks is linear only for very small deformations; like most semiflexible biopolymers [11], it rapidly becomes strongly nonlinear with increasing deformation [5,9,12,13]. One possible cause for this discrepancy is the fact that, in vivo, F-actin is cross-linked with a variety of actin-binding proteins (ABP's), which are essential in determining the elastic properties of the cytoskeleton.…”
mentioning
confidence: 95%
“…The importance of such forces has inspired in vivo studies of the mechanical behavior of cells [1][2][3][4]. These have revealed an intriguing observation: a wide variety of cells exhibits properties well described by soft glassy rheology (SGR), a theory of linear viscoelasticity developed to characterize soft solids with glasslike behavior [3].…”
mentioning
confidence: 99%